Paleomagnetic and geobarometric study of the mid-Cretaceous Whitehorse Pluton, Yukon Territory (Dataset) ... - M. J. Harris; D. T. A. Symons; W. H. Blackburn; C. J. R. Hart (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic and geobarometric study of the mid-Cretaceous Whitehorse Pluton, Yukon Territory ...